Effect off ollicular fluid proteins on post-thaw characteristics of buffalo spermatozoa - KUMARESAN, A; GARG, ABHISHEK; SURESH, V; ANSARI, M R (The Indian Journal of Animal Reproduction, 2023)
Follicular fluid collected from buffalo ovaries obtained from slaughter house was exposed to SDS-PAGE to study theelectrophoretic profiles of follicular proteins (FP). A total number of 28 protein bands were obseived, of which, I 0, I 4 and 4 were of>97, 29-97 and 4 mg/ml) showed inferior spermatozoan characteristics than that of control. Fromthis study it is inferred that FP have a beneficial effect on spermatozoan function in a dose dependent pattern.
Keywords: Follicular fluid; spermatozoa; buffalo; follicular protein